EXPLORING THE UNIVERSITY STUDENTS’ PERFORMANCE ON IELTS SPEAKING PREDICTION TEST: A CASE STUDY - Mulyani, Mulyani; Eridafithri, Eridafithri; Geby, Nofreza Setia; Trisnawati, Ika Kana (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study investigates the students’ performance on the IELTS Speaking Prediction Test among fifth-semester students of the English Education program at Universitas Bina Bangsa Getsempena. This study applied a quantitative approach, in which students participated in an IELTS Speaking Prediction Test, assessing key aspects of speaking skills, including fluency and coherence, lexical resource, grammatical range and accuracy, pronunciation, the ability to deal with questions and body language. The findings reveal that students generally performed well in fluency, pronunciation, ability to deal with questions, and body language, but show variability in lexical resource and grammatical range. The study emphasizes the importance of interaction and feedback in enhancing speaking proficiency. Additionally, the study identifies areas for improvement in vocabulary diversity and grammatical consistency, highlighting the need for targeted intensive practice and valuable feedback. The study concludes that while students possess a strong foundation in basic speaking skills, ongoing and intensive practices and the integration of self-regulated learning strategies are essential for achieving higher performance in the IELTS Speaking test